2012
DOI: 10.1515/jpem-2012-0013
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum anti-Müllerian hormone in adolescents with polycystic ovary syndrome: relationship to ultrasound features

Abstract: Context Serum Anti-Müllerian Hormone (AMH) is linked to the ovarian follicle pool. Little is known about the relationship between serum AMH and ovarian ultrasound (US) features in adolescents with Polycystic Ovary Syndrome (PCOS). Objectives To confirm that serum AMH is elevated in adolescents with PCOS and to correlate serum AMH with ovarian ultrasound features in this population. Design A retrospective chart review of clinical, biochemical, and ultrasonographic data in adolescents with PCOS and normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 60 publications
(55 reference statements)
1
22
0
1
Order By: Relevance
“…It is not only used to measure ovarian reserve but also reflects the greater number of follicles present in the ovaries with polycystic morphology (PCOm). Serum concentrations of AMH correlate with the antral follicle count and degree of menstrual disturbances (86,87,88). The strong association between AMH and follicle count has led some authors to compare the performance of one against the other for the diagnosis of PCOS.…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…It is not only used to measure ovarian reserve but also reflects the greater number of follicles present in the ovaries with polycystic morphology (PCOm). Serum concentrations of AMH correlate with the antral follicle count and degree of menstrual disturbances (86,87,88). The strong association between AMH and follicle count has led some authors to compare the performance of one against the other for the diagnosis of PCOS.…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Four of the seven studies done in adolescents revealed statistically significant differences in ovarian volume between PCOS patients and controls (8, 9, 12, 13). Shah et al and Pawelczak et al revealed that in a cohort of 74 overweight/obese PCOS adolescents, 40% of adolescents had an enlarged ovarian volume (10,14). Ovarian volume was also found to be similar in patients with PCOS and patients with polycystic ovaries but with no clinical manifestations of PCOS (12).…”
Section: Discussion Ovarian Volumementioning
confidence: 94%
“…Overall, nine studies conducted between 2003 and 2013 were identified, and seven were used in this review (8)(9)(10)(11)(12)(13)(14). Two studies were excluded from our analysis because there was a lack of ultrasonographic quantitative data (15,16).…”
Section: Results Of Ovarian Ultrasound Studies In Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations